Debunking Myths of Economic Growth: The Political Economy of VAT Reform in the Asia-Pacific - Haryono, Andi; Marwan, Awaludin (Journal of Contemporary Sociological Issues, 2025)
This article examines the effects of Indonesia's proposed Value-Added Tax (VAT) increase policy, which would raise the tax rate from 11% to 12% starting in January 2025. This policy aims to increase state revenue, reduce the budget deficit, and fund national priority initiatives, including infrastructure development, reducing food dependency, and poverty alleviation. This article demonstrates the efficacy of VAT reform in boosting economic growth through a comparison with Asia-Pacific nations, such as China, Singapore, Japan, and Taiwan. The study's findings suggest that increasing the VAT may enhance state revenue but also reduce people's purchasing power and exacerbate social inequality, particularly in rural areas. To mitigate the effects and improve the effectiveness of policy implementation, this study also identifies best practices from other countries, such as China's incremental changes and Singapore's digitalization of the tax system, which can be applied in Indonesia. This article suggests that Indonesia's VAT increase will generate state revenue but disproportionately burden lower-income populations and deepen inequality unless accompanied by compensatory social protection mechanisms and progressive reforms informed by comparative experiences in the Asia-Pacific region. Keywords: VAT Increase, Economic Growth, Tax to GDP Ratio, VAT Policy Reform, Asia-Pacific Studies